Leadership in Action: Capital Ideas: Enhancing the Power of Human Assets - Yukl, Gary; Lepsinger, Richard (Center for Creative Leadership, 2008)
In today's rapidly changing and competitive business environment, organizations and their leaders must pay attention to an asset that is sometimes given short shrift-human capital, the skills and motivation of the organization's employees. Leaders at all levels can have a strong influence on human capital through a combination of relationsoriented behaviors and human resource management programs.